CIÊNCIA DA INFORMAÇÃO E CIÊNCIA DE DADOS: CONVERGÊNCIAS INTERDISCIPLINARES - Moutinho, Sonia Oliveira Matos [UNESP]; Alencar, Danila Fernandes [UNESP]; Martins, Paulo George Miranda [UNESP]; Coneglian, Caio Saraiva [UNESP] (Univ Federal Santa Catarina, 2024)
objective: Identify the interdisciplinary relationships between the areas of Data Science and Information Science, since Information Science is an interdisciplinary field of study that deals with developing techniques and methods for collecting, storing, retrieving, analyzing and disseminating information. Methods: It is characterized as descriptive, exploratory and bibliographical research, the survey of which took place in interdisciplinary databases at national and international levels. Results: Studies carried out in the field of Data Science have certain interdisciplinary convergences with Information Science, especially in activities that encompass the Data Life Cycle, in which the information professional can contribute with their skills in the stages of collection, storage, retrieval and discard. Therefore, there is a promising scenario in which Information Science can effectively contribute to the development of new skills and possibilities for working in innovative environments for information professionals. Conclusions: It is concluded that, as Data Science continues to develop, information professionals who wish to work in the area need to develop new skills to deal with large volumes of data and new Information and Communication Technologies, consolidating the scientific construct of Information Science, making it possible to contribute to the development of Data Science as a new area of knowledge.
Keywords: Information Science; Interdisciplinarity; Data Science; Data Librarian